THE JUST REGULATION OF IMMATERIAL LOSSES IN SHARIA ECONOMIC DISPUTES: RECONSTRUCTION OF TA'WID BASED ON MAQASID AL-SYARI'AH - Tiya Ulfa; Sukarmi; Nur Chanifah (PT. Radja Intercontinental Publishing, 2026)
This article examines the regulation of immaterial losses in sharia economic disputes and proposes a reconstruction through maqashid al-syariah as an analytical tool. The normative basis for compensation has been recognized through the concepts of ta'wid and daman in the Compilation of Sharia Economic Law (KHES) and the DSN-MUI fatwa, but this formulation stops at the principle and interprets